Massive open on-line courses (MOOCs): global education paradigm shift? - Robert W. Robertson; Carlos Tasso eira de Aquino (Centro de Estudios Financieros, 2017)
Massive open on-line courses or «MOOCs» is the current catchphrase of the on-line education sector. Many see MOOCs as representing a «disruptive innovation» that will change the education. There are many supporters and many cynics who have weighed in on the MOOC debate. This paper provides an overview of the development and evolution of MOOCs with a view to looking at possible future directions that might be available for these types of courses.